2020
DOI: 10.46743/1540-580x/2020.1908
|View full text |Cite
|
Sign up to set email alerts
|

Injury Reporting in Collegiate Soccer Players and the Impact of Non-Reporting

Abstract: Purpose: The purpose of this study was to determine injury reporting rates of collegiate soccer players and explore possible consequences of not reporting these injuries. Methods: Soccer players (male and female) from eight Division II and III schools were surveyed about their injury history during college, injury reporting behavior, and the consequences of their worst non-reported injury. The head coach of each soccer team was also surveyed about their perception of player injury reporting on their team. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…With regards to gender, studies have shown that female soccer players have a higher tendency to sustain concussions compared to male players [10]- [12]. Nevertheless, it has been reported that almost 40% of soccer players who have sustained a concussion during a match did not report the incidence, thereby could lead to negative consequences such as a higher tendency to sustain a further concussion in the following matches [13].…”
Section: Introductionmentioning
confidence: 99%
“…With regards to gender, studies have shown that female soccer players have a higher tendency to sustain concussions compared to male players [10]- [12]. Nevertheless, it has been reported that almost 40% of soccer players who have sustained a concussion during a match did not report the incidence, thereby could lead to negative consequences such as a higher tendency to sustain a further concussion in the following matches [13].…”
Section: Introductionmentioning
confidence: 99%